2015
DOI: 10.5116/ijme.5521.3b2d
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sources of stress among Malaysian dental students

Abstract: ObjectivesThe study objectives were to identify the stress levels and to explore the impact of students' year of study and gender on the perceived sources of stress among Malaysian dental students.MethodsThis was a cross-sectional study involving dental students from year one to year five from private and public universities in Malaysia. The study was formally approved by the Research and Ethics Committee, International Medical University Malaysia. Dental Environment Stress (DES) questionnaire was used for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
66
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 17 publications
17
66
1
13
Order By: Relevance
“…Unfortunately, this is prevailing in many other Saudi Universities 16 , 17 . A recent study reported that the top stressors for undergraduate students are fear of failing a course, examination results, and concerns regarding completion of clinical work 23 . Stress may affect students’ well-being and impacts their academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this is prevailing in many other Saudi Universities 16 , 17 . A recent study reported that the top stressors for undergraduate students are fear of failing a course, examination results, and concerns regarding completion of clinical work 23 . Stress may affect students’ well-being and impacts their academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The most common perceived sources of academic stress, reported by various medical students in the literature, include fear of examinations, concerns about examination results and grades, and fear of failing the course at the end of the semester/year. [32][33][34] The flipped exam model in our study did not just reduce test anxiety, however it also addressed academic and test competence issues, which also represent substantial components associated with academic performance. 31 For instance, academic competence, which refers to a students' ability to manage their study load, 31 was undertaken by allowing the students to employ their understanding of the workshop presentations to design one question that they perceive as essential and relevant to learning.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…Studies have shown that health related quality of life is poor among medical students, 2 and students in their clinical years experience the most negative impact 3 . Muneer and colleagues 4 reported high levels of stress among Malaysian dental students, with fear of failure in a course being ranked as the top stressor. Consequently, students who experience a high level of stress with poor coping strategies during medical school are vulnerable to develop burnout 5 - 7 …”
Section: Introductionmentioning
confidence: 99%